Case report: Neonatal-onset inflammatory bowel disease due to novel compound heterozygous mutations in DUOX2 - Finocchi, Andrea; Pacillo, Lucia; Chiriaco, Maria; Di Matteo, Gigliola; Francalanci, Paola; Angelino, Giulia; Caldaro, Tamara; Rivalta, Beatrice; O’Mara, Maurice; Zhang, Suisheng; Lepri, Francesca Romana; Novelli, Antonio; et al. (Frontiers in Genetics, 2023)
Very Early Onset Inflammatory Bowel Disease (VEO-IBD) is potentially associated with genetic disorders of the intestinal epithelial barrier or inborn errors of immunity (IEI). Dual oxidase 2 (DUOX2), an H2O2-producing NADPH oxidase expressed at apical enterocyte membranes, plays a crucial role in innate defense response. Biallelic DUOX2 mutations have been described only in two patients with VEO-IBD up to date. We report the case of a 1-month female infant who presented persistent high C-reactive protein (CRP) levels from birth and anemia. Positive occult blood and very high calprotectin in the stool were detected and abdominal ultrasound showed thickened last ileal loop. Full endoscopy evaluation revealed important colon stenosis with multiple pseudo-polyploidy formations that resulted refractory to steroid therapy, requiring a partial colic resection. Histological examination of biopsy samples showed morphological features of IBD. Whole Exome Sequencing (WES) disclosed compound heterozygous variants in DUOX2 gene: the pathogenic c.2524C>T; p.Arg842Ter and the variant of uncertain significance (VUS) c.3175C>T; p.Arg1059Cys. Molecular and functional studies showed the presence of mutant DUOX2 in the intestinal epithelium of the patient, albeit with at least 50% decreased catalytic activity. In conclusion, we describe the third patient to date with compound heterozygous variants of DUOX2, as responsible of a monogenic neonatal-IBD. This case expands the knowledge about Mendelian causes of VEO-IBD and DUOX2 deficiency. We suggest that DUOX2 should be part of the diagnostic evaluation of patients with suspected monogenic VEO-IBD.